Efficacy and Safety of Adalimumab in Noninfectious Uveitis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Li, Biao; Li, Haoran; Zhang, Li; Zheng, Yanlin (Frontiers in Pharmacology, 2021)
Background: Patients with noninfectious uveitis (NIU) are at risk of systemic side effects of long-term glucocorticoid therapy and uncontrolled inflammatory complications. In urgent need to identify more aggressive therapies, adalimumab (ADA) may be the right choice. Objectives: To summarize the current evidence from randomized controlled trials (RCTs) regarding the efficacy and safety of ADA in the treatment of NIU. Methods: We searched Pubmed, Embase, Web of Science, Cochrane Library databases, and Clinical Trials Registry for qualifying articles from their inception to November 19, 2020, with no language restriction. Randomized controlled trials comparing ADA with conventional routine treatment in noninfectious uveitis patients of any age, gender, or ethnicity were included. The primary outcome was the time to treatment failure (TF). The secondary outcomes were the change in best-corrected visual acuity (BCVA), change in the anterior chamber (AC) cell grade, change in vitreous haze (VH) grade, and adverse events (AEs). Main results: The six studies comprised 605 participants in all, and the sample size of each study ranged from 16 to 225. The overall pooled results of the primary outcome (HR = 0.51; 95% CI, 0.41 to –0.63) showed that ADA nearly halved the risk of treatment failure compared to placebo for NIU patients. The pooled mean difference of change in BCVA was -0.05 (95% CI, −0.07 to −0.02). The pooled mean difference of change in AC cell grade and VH grade was −0.29 (95% CI, −0.62 to −0.05) and −0.21 (95% CI, −0.32 to −0.11), respectively. The incidence of AEs in the ADA group was numerically higher than that of AEs in the placebo group (2,237 events and 9.40 events per patient-year, equivalent to 1,257 events and 7.79 events per patient-year). Conclusion: This meta-analysis of six RCTs further confirmed that ADA considerably lowered the risk of treatment failure or visual loss, and moderately reduced AC cell grades and VH grades with slightly more AEs, as compared to placebo. ADA is both effective and safe in treating NIU. Systematic Review Registration: [https://clinicaltrials.gov], identifier [CRD42020217909].